Crustacean zooplankton densities in northern temperate lakes are related to habitat temperature across a wide gradient in lake dissolved organic carbon and nutrient content. (22nd February 2023) - Kelly, Patrick T.; Jones, Stuart E.
Abstract: Lake crustacean zooplankton densities often are negatively correlated with terrestrial dissolved organic carbon (DOC) concentrations. These reductions in zooplankton with increased DOC are hypothesised to be linked to diminished resource quantity or lower resource quality as terrestrial material is low in essential nutrients and macromolecules. The impact of DOC on lake physics also potentially reduces available habitat for zooplankton as the warm and well‐oxygenated epilimnion is shallower in lakes with high DOC concentrations. Our goal was to investigate these potential mechanisms to determine the influence of DOC on drivers of zooplankton densities in a survey of north temperate lakes. We sampled crustacean zooplankton densities in 10 lakes that varied in mean DOC concentration from 6 to 27 mg L −1 . We also measured resource availability as chlorophyll concentration, resource quality as essential fatty acid (EFA) concentration and the stoichiometric ratio of carbon‐to‐phosphorus (C:P), and habitat availability as integrated habitat temperature and dissolved oxygen to determine the strongest predictor of zooplankton densities across lakes. In addition, we quantified zooplankton habitat use through Schindler trap profiles through the water column. Zooplankton densities were most strongly related to integrated habitat temperature and were not closely related to measures of resource quantity or quality. Depth of the mix layer was negatively correlated with DOC concentration, yet there was no relationship between DOC concentration and zooplankton habitat use. Overall resource quantity and quality increased across the DOC gradient, as chlorophyll and EFA concentration were greatest in lakes with higher DOC. Our results indicate the potential for physics‐mediated responses between lake DOC and zooplankton density. As lakes with greater DOC concentrations have, on average, shallower mixed layers and colder habitats, zooplankton may either be constrained to a relatively smaller proportion of the catchment or experience reduced temperatures that may delay development or feeding rates. Lake DOC concentrations are projected to increase under future climate scenarios, so accompanying changes in lake temperature profiles are likely to follow. These also may reduce food‐web productivity, as shrinking mixed layers or colder total water columns resulting from steeper thermoclines may reduce habitat availability or suitability for zooplankton communities.